The Effect of Drumstick/Horseradish (Moringa oleiferaLam) Leaves Ethanol Extract to The Mortality of Anopheles aconitus L. Larvae - Maung, Yuzana; Handayani, Sutartinah Sri; .........., Lukman Aryoseto (Nexus Biomedika, 2017)
Introduction: The use of synthetic insecticides to control Anopheles aconitus L. vector has negative impacts to nature dan resistancy, so it is necessary to use botanical larvicides as alternative substance to replace synthetic insecticides. Drumstick/Horseradish (Moringa oleifera Lam) leavesare loaded with saponin, tanin, flavonoid, dan alkaloid which have larvicide effects. The aim of this research was to find out the effect of Moringa oleifera Lam leaves ethanol extract on mortality of Anopheles aconitus L. larvae. Methods: This research is theexperimental laboratoricwith posttest only control group design which was conductedon 08-17 November 2016 at B2P2VRP, Salatiga, Central Java. In this research, ethanol extract of Moringa oleifera Lam leaves was used as larvicide to Anopheles aconitus L. third instar larvae. Larva was divided into 6 groups, each group contained 25 larvaes. For one control group was added 100ml distilled water,while the other 5 groups were added different concentration level of Moringa oleifera Lam leaves ethanol extract (1, 10, 20, 30, 40 mg per 100 ml of distilled water). Each test groups were repeated 4 times in this research. Observation was conducted after 48 hours exposure of extract and the numbers of larvae mortility were counted ofeach experimental group. The data were analyzed by using Kruskal-Wallis dan Probit tests. Results:The result of data analyzed by Kruskal-Wallis test indicates that there was significant difference on theaverage mortility of Anopheles aconitus L. larvae among 6 experimental groups. The result of Probit analysis indicate 50% of larvae mortality in 83.675 mg/100 ml (LC50) and 90% in 15318.159 mg/100 ml (LC90). Conclusions:Drumstick/Horseradish (Moringa oleifera Lam) leaves ethanol extract has mortalityeffect on Anopheles aconitus L. third instar larvae. Keywords: ethanol extract of Drumstick/Horseradish leaves, larvicide, Anopheles aconitus L. third instar larvaeÂ